A novel crucible-less inert gas atomisation method of producing titanium powder for additive manufacturing. (1st January 2019) - Zheng, Mingyue; Zhang, Shaoming; Hu, Qiang; Xu, Jun; Mao, Weimin; Lu, Liangliang; He, Huijun; Liu, Yingjie; Zhao, Wendong
ABSTRACT: A novel low-cost gas atomisation technology producing spherical titanium powder (wire induction heating gas atomisation, WIGA) has been developed for additive manufacturing. Combined with the gas atomisation principle, the characteristics of WIGA were analysed. The effects of the gas pressure, metal temperature and the wire-feeding speed on the particle size of the titanium powder were studied. The results indicated that the decreases in mass median particle diameter (D50 ) and the increases in efficiency of fine size powders occurred with the increase in gas atomisation pressure and melting temperature and with the decrease of wire-feed speed. The optimum parameters are that the main gas pressure (P0 ) is 4.0 MPa, the degree of superheat of the metal melt is 350°C and the wire-feed speed is 50 mm s −1 . On the condition, the D50 of titanium powder was 40.2 μm and powder morphology was spherical. Satellites rarely existed on the surface of particles.